Peter I and the Birth of the Russian Empire: Political Leadership and Military Successes in Comparative Perspective - A. Dimitrov; G, Durev (Vestnik MGIMO-Universiteta)
Empires are usually born through political recognition and extensive military successes. The ruler’s personality and the activities of political and military advisors and generals are crucial for the emergence of an empire. The authors argue that in the case of Peter the Great (Peter I), the political recognition and military successes were achieved simultaneously in the east and west, however, in different contexts. The authors make a series of comparisons between Peter I and other monarchs of the epoch, such as Carl XII, August II, Frederick I, Carlos II, Willem III, Leopold VI, and others, relying on three main categories, namely education, “vices and virtues” and political views. This comparison is necessary to highlight the essential prerequisites in Peter’s personal development that might have determined his political actions. In addition, the article carries out an evaluation of the geopolitical significance of the military campaigns and victories achieved by the tzar and his commanders. These achievements are substantiated to correlate with Russian rise as a great power directly. After the Peace of Nystad, the geopolitical interests of the Tsardom were finally met, with the territorial dominium of the Empire being outlined for a century ahead.Furthermore, the territorial expansion was accompanied by the exercise of the “imperium” as a political authority exclusive to the Russian monarchs. The authors try to highlight the connection between the personal development of monarchs, their achievements, and imperial ambitions. The comparative analysis of these factors in various imperial cases provides additional considerations for understanding the historical period.